중국인 유학생의 대한국 정치적 인식 변화에 관한 연구 : 한중 정치적 관계를 중심으로 - 洪廷倫; Hong Jungryun (중소연구, 2022)
본 논문은 재한 중국인 유학생이 유학 전후 한국에 대해 어떤 인식을 가지고 있는지 파악하고자 한다. 조사에 의하면 한국에서 유학하는 중국인 유학생은 대부분 한국에 대해 호감이 있다. 정치적 요인은 중국인 유학생에게 유학 전에는 상대적으로 영향을 덜 미치지만 유학 후에는 더 크게 영향을 미치고 있다. 중국인 유학생들은 북한의 핵무기 개발이나 미사일 발사가 한국의 안보에 위협이 된다는 점을 공감하면서도 사드 배치가 중국의 안보에 위협을 준다는 입장을 가지고 있다. 또한, 사드 배치 후 중국이 자국내 한국의 대중문화에 대해 취한 조치를 지지하면서도 향후 양국 관계가 개선되기를 희망하고 있다. This paper aims to understand what perception Chinese international students in Korea have about Korea before and after studying in Korea. According to the survey, most Chinese students studying in Korea have a favorable impression of Korea. Political factors have a relatively less influence on Chinese international students before studying abroad, but a greater influence after studying abroad. Chinese students agree that North Korea's nuclear weapons development or missile launches pose a threat to South Korea's security, but say the THAAD deployment poses a threat to China's security. It also supports China's sanctions against Korean pop culture after the THAAD deployment, but hopes to improve bilateral relations in the future.